Disappearing Help Text: Implementing a Note-Based Tool for In-Line Clinical Decision Support and Note Bloat Reduction - Chong, Amy Z.; Lee, Begem; Hollenbach, Kathryn; Kuelbs, Cynthia L. (Applied Clinical Informatics, 2022)
Objective The authors describe a novel solution to the challenges of lengthy notes and poor note readability by creating an unobtrusive clinical decision support tool named “disappearing help text.”Methods We designed this tool in Pediatric Hospital Medicine (PHM) note templates to provide in-line decision support on best documentation practices, note bloat reduction, billing compliance, and provider workflow enhancement.Results After template changes that utilized disappearing help text, we reduced the percent of notes utilizing any laboratory SmartLink from 90.2 to 15.3% for admission notes (p <0.001), 92.6 to 17.8% for progress notes (p <0.001), and 14 to 7.2% for discharge summaries (p <0.001). In admission and progress notes, this correlated with a significant reduction in the median note length as a proxy of note bloat reduction, with a 18.7% character count reduction in progress notes (p <0.001) and a 6.4% reduction in admission notes (p <0.001). PHM coding queries decreased from an average of 42 per month to 36 per month, and there was no change in PHM attending billing compliance audit performance.Discussion Note template changes that utilized disappearing help text significantly reduced the length of both progress and admission notes, a proxy for note bloat reduction, without negatively impacting coding query frequency or internal billing audit performance. One factor that likely contributed to this reduction in note length is the reduced usage of laboratory SmartLinks prompted by disappearing help text.Conclusion We present the use of in-line disappearing help text embedded into note templates as a clinical decision support tool to improve note readability, educate trainees on note documentation, and protect confidential teen information. Help text implementation correlated with a reduction in the automatic insertion of laboratories into notes and a decrease in note character count.
Keywords: clinical documentation and communications; encounter level; notes; discharge summary; electronic health record; confidentiality; clinical decision support; physician